2017
DOI: 10.21746/ijbio.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antibiotic resistance and enterotoxigenic potential of Staphylococcus aureus strains isolated from foods sold by street vendors in Gaborone, Botswana

Abstract: Staphylococcus aureus is one of the causes of foodborne diseases worldwide. Staphylococcal food poisoning ensues after ingestion of contaminated food and results in symptoms of gastroenteritis such as vomiting, abdominal cramps and diarrhea. The present paper aims to isolate Staphylococcus aureus from foods sold by street vendors in Gaborone, Botswana, and to determine its enterotoxigenic potential and antibiotic resistance profile. One hundred eight food samples comprising starch, meat, salads and vegetables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…22 Researchers have reported relatively high levels of contamination of ready-to-eat and street foods with S. aureus. 23,24 However, in some studies, low contamination rates of street foods have been reported. 25 Differences between our results and those obtained in other studies may be due to the studied food types (samosa and falafel) since poor personal hygiene habits in hand-processed foods may be associated with S. aureus contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Researchers have reported relatively high levels of contamination of ready-to-eat and street foods with S. aureus. 23,24 However, in some studies, low contamination rates of street foods have been reported. 25 Differences between our results and those obtained in other studies may be due to the studied food types (samosa and falafel) since poor personal hygiene habits in hand-processed foods may be associated with S. aureus contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies on sea, it was reported as the most prevalent enterotoxin encoding gene 9,29 ; however, in some other studies on sec and sed genes, prominent enterotoxin genes were found. 23,30 Differences in the distribution of enterotoxin encoding genes could be due to the ecological origins and geographical varieties of S. aureus isolated from foods, livestock, and humans. 31 In our study, tst gene was also detected in 12.5% of the samples, suggesting that contamination could occur through food handling by carriers of TSST-positive S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation